Transposase N-terminal phosphorylation and asymmetric transposon ends inhibit piggyBac transposition in mammalian cells. Issue 22 (20th December 2022) - Luo, Wentian; Hickman, Alison B; Genzor, Pavol; Ghirlando, Rodolfo; Furman, Christopher M; Menshikh, Anna; Haase, Astrid; Dyda, Fred; Wilson, Matthew H
Abstract: DNA transposon systems are widely used in mammalian cells for genetic modification experiments, but their regulation remains poorly understood. We used biochemical and cell-based assays together with AlphaFold modeling and rational protein redesign to evaluate aspects of piggyBac transposition including the previously unexplained role of the transposase N-terminus and the need for asymmetric transposon ends for cellular activity. We found that phosphorylation at predicted casein kinase II sites in the transposase N-terminus inhibits transposition, most likely by preventing transposase–DNA interactions. Deletion of the region containing these sites releases inhibition thereby enhancing activity. We also found that the N-terminal domain promotes transposase dimerization in the absence of transposon DNA. When the N-terminus is deleted, the transposase gains the ability to carry out transposition using symmetric transposon left ends. This novel activity is also conferred by appending a second C-terminal domain. When combined, these modifications together result in a transposase that is highly active when symmetric transposon ends are used. Our results demonstrate that transposase N-terminal phosphorylation and the requirement for asymmetric transposon ends both negatively regulate piggyBac transposition in mammalian cells. These novel insights into the mechanism and structure of the piggyBac transposase expand its potential use for genomic applications. Graphical Abstract: